Eksplorasi Pengalaman Mahasiswa BKPI dalam Menggunakan ChatGPT dan Implikasinya terhadap Berpikir Kritis - Syarifah Aini Rambe; Nabila Arini; Melsina Raini (Malewa: Journal of Multidisciplinary Educational Research, 2026)
This study aims to explore the perceptions of Islamic Guidance and Counseling Education (BKPI) students regarding the use of ChatGPT in enhancing critical thinking skills. The study employed a qualitative approach with a phenomenological research design. The participants consisted of 40 second-semester BKPI students at IAIN Takengon, selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, while data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the use of ChatGPT has both positive and negative impacts on students. Positively, ChatGPT helps students understand course materials, stimulates cognitive development, broadens knowledge, facilitates information retrieval, and supports the completion of academic tasks. However, the study also found a tendency toward dependency on ChatGPT, reduced independent analytical efforts, and a decline in the ability to evaluate and critically assess information when the technology is used excessively without reflection and verification. Therefore, the use of ChatGPT should be carried out wisely and accompanied by proper guidance to optimize the development of students' critical thinking skills. Keywords: Student Perceptions, ChatGPT, Critical Thinking, Artificial Intelligence, Phenomenology.